2013
DOI: 10.3390/ijerph10083121
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Bullying among Healthcare Workers

Abstract: This paper aims to assess consistent predictors through the use of a sample that includes different actors from the healthcare work force to identify certain key elements in a set of job-related organizational contexts. The utilized data were obtained from the 5th European Working Conditions Survey, conducted in 2010 by the European Foundation for the Improvement of Living and Working Conditions. In light of these objectives, we collected a subsample of 284 health professionals, some of them from the Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
5
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(119 citation statements)
references
References 75 publications
5
98
5
4
Order By: Relevance
“…The data obtained from 5th European Working Conditions Survey conducted in 2010 showed that the prevalence of workplace bullying was 11.3% among the employees in the healthcare sector [7]. The research on workplace bullying solely among physicians is rather limited as compared to the extent of the investigations in the samples of nurses or healthcare sector in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data obtained from 5th European Working Conditions Survey conducted in 2010 showed that the prevalence of workplace bullying was 11.3% among the employees in the healthcare sector [7]. The research on workplace bullying solely among physicians is rather limited as compared to the extent of the investigations in the samples of nurses or healthcare sector in general.…”
Section: Discussionmentioning
confidence: 99%
“…This variation could be explained by cultural differences, diverse level of knowledge of the phenomenon, the inconsistency of bullying measurement methods and the variety of instruments used worldwide [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Não foi verifi cada correlação significativa entre assédio moral e idade, este resultado corrobora o estudo Maciel et al (2007); Soares e Oliveria (2012) e Kivimaki et al (2000) e se opõe ao encontrado por Ariza-Montes et al (2013a), que verifi caram que profi ssionais mais jovens sofrem mais assédio moral. Pode se hipotetizar que profi ssionais mais jovens ocupem posições hierárquicas mais baixas em virtude da pouca experiência, e este fato os tornem vítimas mais frequentes ou, ainda, que os jovens tenham maior propensão a não seguir regras institucionais e mesmo sociais e entrem em confronto com os superiores, porém a maioria dos estudos não tem dado suporte a essa a hipótese.…”
Section: Média Desvio-padrão E Intervalo De Confi Ança Da Pontuação unclassified
“…Certas características físicas ou psicológicas ou traços de personalidade poderiam predispor ao agressor e ao agredido (Ariza-Montes et al, 2013a). Pessoas que são marginalizadas pela sociedade, pertencentes a minorias, como certos grupos raciais ou religiosos, mulheres, homossexuais, portadores de necessidades especiais ou classes sociais mais baixas são alvos de preconceito, e essa tendência pode se repetir nas organizações que são uma extensão das relações sociais.…”
unclassified
“…Bullying is widely recognized as a persistent problem in the profession of nursing (Ariza-Montes, Muniz, Montero-Simó, & Araque-Padilla, 2013; Berry, Gillespie, Gates, & Schafer, 2012; Chipps, Stelmaschuk, Albert, Bernhard, & Holloman, 2013). Those at particular risk include individuals with limited authority and experience such as nursing students (Clarke, Kane, Rajacich, & Lafreniere, 2012; Hakojarvi, Salminen, & Suhonen, 2014; Kern, Montgomery, Mossey, & Bailey, 2014).…”
mentioning
confidence: 99%